VILLAGE GOVERNMENT PERFORMANCE TO IMPROVE POPULATION ADMINISTRATION SERVICES IN WANGUN VILLAGE, PALANG-TUBAN DISTRICT - Putri Rahayu, Hilfa (INDONESIAN JOURNAL OF SOCIAL POLITIC AND POLICY STUDIES, 2024)
In Law Number 6 of 2014 it tries to return the concept and form of the Village as it originates, the Village or is called by another name, is a legal community unit that has the authority to regulate and administer the interests of the local community based on recognized local origins and customs in the national government system and are in the District Region. Villages can be formed, deleted, and/or merged with due observance of their origin at the initiative of the community with the approval of the Regency Government and DPRD. Substantively the Village Law This implies an effort to empower village government apparatus and also the community village. Village Government or in the form of other names such as Marga Government, its existence is dealing directly with the community, as the spearhead foremost government. Implementation of village autonomy characterized by good service either can provide satisfaction for people who need it because it's fast, easy, precise and at an affordable cost, therefore implementation in the field must be supported by the factors involved in the implementation of the village policy. Perception officials regarding their work depends on the level of intrinsic and extrinsic outcomes and how workers/employees view these outcomes and reflect attitudes toward them his job. Mental attitude is a mental condition that encourages someone to strive to achieve maximum work potential. The performance of the Wangun village government has not quite good in terms of productivity, service quality and service accountability from the aspect of mental attitude and behavior of village officials in the management of certificates towards society.